The Role Of Self-Efficacy And Employee Engagement On Organizational Citizenship Behavior Transmitted Through Organizational Commitment At PT Geoservices Banjarbaru - Elza Fammay Juniar; Majang Palupi (Cita konsultindo, 2025)
This study aims to examine the relationship and role of self-efficacy and employee engagement on organizational citizenship behavior transmitted through organizational commitment. This study is focused on employees at PT Geoservis Banjarbaru. This study uses a quantitative approach with a questionnaire method and obtained 60 respondents who are employees of PT Geoservis Banjarbaru. The data analysis technique in this study uses the Structural Equation Modeling (SEM) method with Partial Least Square (PLS). The findings of this study prove that 1) Self Efficacy, Employee Engagement, and Organizational Commitment have a positive and significant effect on organizational engagement behavior 2) Self Efficacy and employee engagement have a positive and significant effect on organizational commitment 3) Organizational commitment is able to mediate the relationship between self-efficacy and organizational citizenship behavior, and 4) Organizational commitment is able to mediate the relationship between employee engagement and organizational citizenship behavior.